Long-term safety and efficacy of benralizumab in patients with severe, uncontrolled asthma: 1-year results from the BORA phase 3 extension trial. Issue 1 (January 2019) - Busse, William W; Bleecker, Eugene R; FitzGerald, J Mark; Ferguson, Gary T; Barker, Peter; Sproule, Stephanie; Olsson, Richard F; Martin, Ubaldo J; Goldman, Mitchell; ,
Summary: Background: Benralizumab is an interleukin-5 receptor α-directed cytolytic monoclonal antibody that has been shown to safely reduce exacerbations and improve lung function for patients with asthma. We assessed the long-term safety and efficacy of benralizumab for patients with severe, uncontrolled eosinophilic asthma. Methods: We conducted a randomised, double-blind, parallel-group, phase 3 extension study at 447 sites in 24 countries. Eligible patients had to have completed the SIROCCO or CALIMA trials and remained on subcutaneous benralizumab 30 mg every 4 weeks (Q4W) or every 8 weeks (Q8W). Patients who had received placebo in those trials were re-randomised in a 1:1 ratio, using an interactive web-based system, to benralizumab 30 mg either Q4W or Q8W (first three doses 4 weeks apart). Treatment lasted for 56 weeks for adult patients (age ≥18 years) and 108 weeks for adolescent patients (age 12–17 years). The primary endpoint was the safety and tolerability of the two dosing regimens of benralizumab up to 68 weeks for adult patients (including the follow-up visit post-treatment) and up to 56 weeks for adolescent patients. This endpoint was assessed in the full analysis set, which included all patients from the SIROCCO and CALIMA predecessor studies who received at least one dose of study treatment in BORA and did not continue into another trial. This study is registered withClinicalTrials.gov (NCT02258542 ). Findings: Between Nov 19, 2014, and July 6, 2016, we enrolled 1926 patients, of whom 633 had received benralizumab Q4W and 639 had received benralizumab Q8W in SIROCCO or CALIMA. The remaining 654 patients had received placebo in those trials and were randomly re-assigned in this trial to receive benralizumab Q4W (n=320) or Q8W (n=334). 1576 patients, including 783 who received benralizumab Q4W (265 newly assigned) and 793 who received benralizumab Q8W (281 newly assigned), were included in the full analysis set. The most common adverse events in all groups were viral upper respiratory tract infection (14–16%) and worsening asthma (7–10%). The most common serious adverse events were worsening asthma (3–4%), pneumonia (<1% to 1%), and pneumonia caused by bacterial infection (0–1%). The percentages of patients who had any on-treatment adverse event, any serious adverse event, or any adverse event leading to treatment discontinuation during BORA were similar between patients originally assigned benralizumab and those originally assigned placebo and between benralizumab treatment regimens. The percentage of patients who had any adverse event was similar between SIROCCO or CALIMA (71–75%; benralizumab group only) and BORA (65–71%), as was the percentage of patients who had an adverse event that led to treatment discontinuation (2% in SIROCCO and CALIMA vs 2–3% in BORA). Interpretation: The 2 years of safety results validate that observations observed in the first year of benralizumab continued through a second year of treatment. No new consequences of long-term eosinophil depletion occurred, and the incidence of other adverse events, including opportunistic infections, were similar during the second year. Funding: AstraZeneca and Kyowa Hakko Kirin.